Efficiency comparison of an isoeugenol-derivated compound, eugenosedin-A, with glibenclamide and pioglitazone in protecting cardiovascular dysfunction of diabetic SHR. Issue 5 (4th May 2023) - Hao, Chi-Long; Lin, Hui-Li; Cheng, Pei-Wen; Tu, Yi-Chen; Yeh, Bor-Chun; Wu, Bin-Nan; Shen, Kuo-Ping
Abstract: This study was to investigate three agents possible protective effect against DM-induced cardiovascular dysfunction in spontaneously hypertensive rats (SHR). Control group was fed normal diet, DM group was injected with STZ/NA and fed high fat diet (HFD), and treatment groups were given STZ/NA, fed HFD, and then oral gavaged with eugenosedin-A (Eu-A), glibenclamide (Gli), or pioglitazone (Pio) 5 mg/kg/per day for 4-week, respectively. Eu-A, Gli, and Pio clearly ameliorated the changes of body weight, cardiac weight, and the biochemical parameters, cardiovascular disorders and inflammation. Like Gli and Pio, Eu-A may be effectively to control DM and the cardiovascular dysfunction. Graphical Abstract: UF0001